Mitochondrial DNA based phylogeny and haplotype networking of European honeybee Apis mellifera L. In Bangladesh - Jannatul Yeasmin Joaty,; Md. Mamunur Rahman,; Md. Ruhul Amin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The European honeybee, Apis mellifera L. is the most widely used species in apiculture. Bangladesh can be suggested as evolutionary significant zone based on the global analysis of its diversity. In the world, there are 33 different A. mellifera subspecies, of which 11 are widely utilized. The present study aims to reveal the genetic diversity, distribution pattern and haplotype networking of the available A. mellifera subspecies in Bangladesh. The sampling was carried out from 18 localities of Bangladesh based on nectarine sources and the molecular analysis was conducted using 609 bp of mitochondrial Cytochrome oxidase subunit-1 (COI) genes. The phylogenetic analysis based on Neighbor-Joining and Maximum-Likelihood compositions from 18 nucleotide sequences (MW428209-MW428226) of the collected samples revealed 7 types of A. mellifera subspecies for the first time in Bangladesh. A total of 82 variable sites of nucleotide composition were observed of which 26 sites were parsimony informative. Remarkable genetic diversity and distribution patterns appeared in central and southern regions of Bangladesh mediated through A. mellifera adami, A. mellifera capensis and A. mellifera sicula. A. mellifera macedonica, implying the diversification and habituation of A. mellifera subspecies in the Bangladesh context. The haplotype diversity of the identified A. mellifera subspecies detected 14 new haplotypes (COIH05-COIH18) for the first time in Bangladesh. Haplotype networking pattern inferred the recent expansion of population in this geographical proximity along with the phylogeographic distribution of the recent A. mellifera clades in different parts of the world. The findings of this study will provide reliable molecular information in the world honeybee gene pool about the diversified occurrence of A. mellifera subspecies in this country and will shed light on the implication of its uses for modernizing the apiculture sector of Bangladesh.